PROGRESSIVE HERMENEUTICS: A COMPARATIVE ANALYSIS OF FAZLUR RAHMAN AND KHALED M. ABOU EL FADL’S METHODOLOGY IN INTERPRETING THE QUR’AN - Fadhilah, Nur; Yusuf, Muhamad Rizky Akbar; Zahiyah, Dwi Zalfa (INTIHA: Islamic Education Journal, 2025)
This study examines the progressive Islamic hermeneutics of Fazlur Rahman and Khaled M. Abou El Fadl, focusing on their methodologies in interpreting the Qur'an. The background highlights the necessity for contemporary Islamic thought to address modern challenges while remaining rooted in authentic tradition. The research objectives are to compare and contrast Rahman's and Abou El Fadl's interpretative frameworks, identifying key similarities and differences in their approaches. Using a comparative analysis methodology, this research delves into their respective hermeneutical principles, the socio-historical context of their interpretations, and the application of their processes to specific Qur'anic texts. The results showed that both scholars emphasize contextual understanding and ethical considerations; Rahman advocates a double movement theory and historical contextualization, whereas Abou El Fadl focuses on the moral trajectory of the text and interpretive pluralism. The conclusion suggests that integrating the insights from both methodologies can offer a more nuanced and adaptable approach to contemporary Qur'anic interpretation, contributing significantly to progressive Islamic thought.